2022
DOI: 10.1186/s41687-022-00470-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the SPUR tool: a profiling instrument for patient treatment behavior

Abstract: Background Long-term treatment adherence is a worldwide concern, with nonadherence resulting from a complex interplay of behaviors and health beliefs. Determining an individual’s risk of nonadherence and identifying the drivers of that risk are crucial for the development of successful interventions for improving adherence. Here, we describe the development of a new tool assessing a comprehensive set of characteristics predictive of patients’ treatment adherence based on the Social, Psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Through the design and delivery of an international multi-arm series of studies in line with the COSMIN criteria, the SPUR tool has been developed as a holistic PROM to assess medication adherence behaviour in patients with long-term conditions. The proposed SPUR model framework 31 and initial model development 32 process have been reported previously. Furthermore, psychometric properties for populations based in the US 33 and France 34 have been reported, in addition to a UK-based cohort of patients living with type 2 diabetes (VMATT2) 35 that produced a more concise SPUR tool – SPUR-27.…”
Section: Introductionmentioning
confidence: 99%
“…Through the design and delivery of an international multi-arm series of studies in line with the COSMIN criteria, the SPUR tool has been developed as a holistic PROM to assess medication adherence behaviour in patients with long-term conditions. The proposed SPUR model framework 31 and initial model development 32 process have been reported previously. Furthermore, psychometric properties for populations based in the US 33 and France 34 have been reported, in addition to a UK-based cohort of patients living with type 2 diabetes (VMATT2) 35 that produced a more concise SPUR tool – SPUR-27.…”
Section: Introductionmentioning
confidence: 99%
“…The initial model to holistically address four key drivers of MA, known as SPUR, was developed by Observia, an e-health organisation based in Paris. 19,20 The four key domains of MA termed Social, Psychographic, Usage, and Rational comprise the 45-item measure and can be used to evaluate individual factors and behaviours related to non-adherence. 21,22 Recently, a shorter 27-item version of the SPUR tool (SPUR-27) was validated for patients living with type 2 diabetes in a UK study by Wells et al 23 The revised 27-item model demonstrated greater reliability than the original SPUR-45 tool as well as significant correlations with objective and PROMs of MA in addition to socio-clinical factors such as body mass index (BMI) and income.…”
Section: Introductionmentioning
confidence: 99%